2007
DOI: 10.1542/peds.2006-2089i
|View full text |Cite
|
Sign up to set email alerts
|

The Health and Well-being of Adopted Children

Abstract: OBJECTIVE. We compared the health and well-being of adopted and biological children and examined whether observed differences may be a result of differences between these 2 groups in demographic characteristics and special health care needs. METHODS. The 2003 National Survey of Children's Health was funded by the Maternal and Child Health Bureau, Health Resources and Services Administration, and was conducted as a module of the State and Local Area Integrated Telephone Survey by the National Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 13 publications
0
40
0
Order By: Relevance
“…1,5,30,31 Care should be used when approaching the newly adopted child, particularly for internationally • Substandard housing, multiple changes in residence • Family members using illegal substances or alcohol, domestic violence ○ Passive tobacco exposure, methamphetamines, other illicit substances in the home environment ○ Other environmental toxins, both in the home and in the surrounding community • Number of prior placements, quality of such care…”
Section: Initial Physical Examinationmentioning
confidence: 99%
See 1 more Smart Citation
“…1,5,30,31 Care should be used when approaching the newly adopted child, particularly for internationally • Substandard housing, multiple changes in residence • Family members using illegal substances or alcohol, domestic violence ○ Passive tobacco exposure, methamphetamines, other illicit substances in the home environment ○ Other environmental toxins, both in the home and in the surrounding community • Number of prior placements, quality of such care…”
Section: Initial Physical Examinationmentioning
confidence: 99%
“…For these children, early scores may not be predictive of later functioning, as seen in studies by Rutter et al 40 Several studies have demonstrated significant developmental delays in children as they enter foster care, particularly in speech and language. 2,5,[41][42][43] Likewise, children adopted internationally nearly always demonstrate delays in at least one area of development, with nearly half of the children having global delays. 13,[44][45][46] Children adopted internationally may demonstrate delays in expressive and receptive language that are not solely related to acquisition of a new language.…”
Section: Age Determinationmentioning
confidence: 99%
“…Studies have shown that adopted children, as a population, tend to experience more health problems than nonadopted children as a population. 8,9 Given recent emphases by respected medical bodies such as the US Centers for Disease Control and Prevention on the importance of family medical history, one might argue that because adopted children often lack access to reliable family medical history, the balance of benefits and risks is different. Certainly, the American Academy of Pediatrics has taken a position to the contrary, explicitly recommending that genetic testing for adopted children be approached in the same way as it is for nonadopted children.…”
mentioning
confidence: 99%
“…11,16 Many adopted children have complex medical, developmental, behavioral, educational, and psychological challenges. 1,2,7,16,17 In fact, 39% of adopted children were classified as having special health care needs, compared with 19% in the general population. 1 Furthermore, more than half of children adopted from foster care (54%) were considered to have special health care needs.…”
mentioning
confidence: 99%